(untitled) (International relations and international law Journal, 2019)
Abstract. Relations between the Russian Federation and the Central Asian countries have always been of strategic importance for both sides. The topic of the study is interesting because against the background of historical events, in the absence of experience in the conduct of foreign policy only by the newly independent Central Asian countries and building their own ways of development, it is possible to trace changes in the conceptual foundations of foreign policy and strategy of the Russian Federation in relation to this region. Despite the twenty-eight years since the collapse of the Soviet Union, there remains a high degree of interdependence between Russia and the Central Asian States. This is due not only to the large extent of the common state borders, but also to the common economic policy promoted both within the framework of the Eurasian Economic Union and on a bilateral basis. Thus, the Central Asian region is a major supplier of energy resources to Russia, through the territory of which raw materials are transported to the countries of the European Union, while Russia exports mineral products, machinery and equipment to the Central Asian countries. However, it is worth noting that, despite the efforts made by the Russian authorities to establish relations with the Central Asian States on a bilateral and multilateral basis, to this day there is no single separately developed concept that would determine the long-term strategy of the Russian Federation in Central Asia. It is no secret that official conceptual sources are required for the study of relations between countries, but since there is no single document of the strategy in relation to the Central Asian countries in the Russian Federation, it is necessary to turn to other concepts. Thus, in this article the authors examined the evolution of the conceptual basics of foreign policy and strategy of Russia towards Central Asian countries with which it is possible to identify stages of relationships, the strategic goals of the Russian Federation and the region’s place in Russian foreign policy. Key words: Russian Federation, Central Asia, foreign policy concept.